Role of Basal Ganglia in Sleep–Wake Regulation: Neural Circuitry and Clinical Significance - Vetrivelan, Ramalingam; Qiu, Mei-Hong; Chang, Celene; Lu, Jun (Frontiers in Neuroanatomy, 2010)
Researchers over the last decade have made substantial progress toward understanding the roles of dopamine and the basal ganglia (BG) in the control of sleep–wake behavior. In this review, we outline recent advancements regarding dopaminergic modulation of sleep through the BG and extra-BG sites. Our main hypothesis is that dopamine promotes sleep by its action on the D2 receptors in the BG and promotes wakefulness by its action on D1 and D2 receptors in the extra-BG sites. This hypothesis implicates dopamine depletion in the BG (such as in Parkinson's disease) in causing frequent nighttime arousal and overall insomnia. Furthermore, the arousal effects of psychostimulants (methamphetamine, cocaine, and modafinil) may be linked to the ventral periaquductal gray (vPAG) dopaminergic circuitry targeting the extra-BG sleep–wake network.